Serum uric acid and the risk of major adverse cardiovascular events and death among older adults: a population-based prospective cohort study - Douros, Antonios; Barghouth, Muhammad H.; Ferrari, Damiano; Ebert, Natalie; Mielke, Nina; Schaeffner, Elke (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background The relationship between serum uric acid (SUA) and adverse outcomes in advanced age remains poorly understood. Our population-based prospective cohort study assessed the potential association between SUA levels and the risk of major adverse cardiovascular events (MACE) and all-cause mortality among community-dwelling older adults. Methods We used data from the Berlin Initiative Study linked to administrative claims and vital statistics. Cohort members were followed from cohort entry (2009) until the occurrence of a study outcome or the end of the study period (2021). We created three exposure groups according to the baseline SUA distribution (in mg/dL; lower: 1.68–5.16, intermediate: 5.17–6.83, higher: 6.84-13.0); SUA levels were updated biennially. Time-dependent Cox models yielded hazard ratios (HRs) and 95% confidence intervals (CIs) of MACE and all-cause mortality adjusted for potential confounders. Sensitivity analyses addressed time-dependent confounding. Results Our cohort included 2,058 individuals (mean age 80 years, 53% female). Lower vs. intermediate SUA levels were not associated with the risk of MACE (HR, 1.16; 95% CI, 0.88–1.54) or all-cause mortality (HR, 1.06; 95% CI, 0.86–1.31). Higher vs. intermediate SUA levels were not associated with the risk of MACE (HR, 1.11; 95% CI, 0.85–1.45) but with an increased risk of all-cause mortality (HR, 1.26; 95% CI, 1.03–1.53). Sensitivity analyses showed no statistically significant associations between higher vs. intermediate SUA levels and the risk of mortality (HR [95% CI]: 1.09 [0.89–1.34] & 1.07 [0.86–1.34]). Conclusion Lower or higher SUA levels are not associated with the risk of MACE or all-cause mortality in older adults.